Pharmacogenetics and Predictive Testing of Drug Hypersensitivity Reactions - Böhm, Ruwen; Cascorbi, Ingolf (Frontiers in Pharmacology, 2016)
Adverse drug reactions ADR occur in approximately 17% of patients. Avoiding ADR is thus mandatory from both an ethical and an economic point of view. Whereas pharmacogenetics changes of the pharmacokinetics may contribute to the explanation of some type A reactions, strong relationships of genetic markers has been shown also for drug hypersensitivity belonging to type B reactions. We present the classifications of ADR, discuss genetic influences and focus on delayed-onset hypersensitivity reactions, i.e., drug-induced liver injury (DILI), drug-induced agranulocytosis (DIA) and severe cutaneous ADR (SCAR). A guidance how to read and interpret the contingency table is provided as well as an algorithm whether and how a test for a pharmacogenetic biomarker should be conducted.